2022
DOI: 10.1108/ijoa-11-2021-3049
|View full text |Cite
|
Sign up to set email alerts
|

The role of empowering leadership and psychological empowerment on nurses’ work engagement and affective commitment

Abstract: Purpose This study aims to investigate to role of empowering leadership and psychological empowerment on nurses' work engagement and affective commitment. Design/methodology/approach Self-administered questionnaire data from 231 nurses working in a university hospital in Saudi Arabia were analysed using a cross-sectional research design using structural equation modelling (SEM) to assess the relationship between empowering leadership (EL), affective commitment (AC) and work engagement (WE) while testing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 141 publications
2
18
0
4
Order By: Relevance
“…Their study confirms the employees' psychological empowerment in general, but not explicitly in relation to managerial work. Similarly, Bobbio et al (2012) and Al Otaibi et al (2022) confirmed the importance of empowering leadership in health care, which indicates that employees are empowered to lead their own work. All six studies (Al Otaibi et al, 2022;Bobbio et al, 2012;Bonias et al, 2010;Leggat et al, 2010Leggat et al, , 2011McAlearney et al, 2011) emphasized the importance of investigating psychological empowerment as an effect of organizational initiatives to support empowerment; in other words, micro-level studies of employees are important for understanding the effects of organizational initiatives such as highperformance work systems (HPWS).…”
Section: Previous Research On Empowerment Of Clinical Staff In Health...mentioning
confidence: 80%
“…Their study confirms the employees' psychological empowerment in general, but not explicitly in relation to managerial work. Similarly, Bobbio et al (2012) and Al Otaibi et al (2022) confirmed the importance of empowering leadership in health care, which indicates that employees are empowered to lead their own work. All six studies (Al Otaibi et al, 2022;Bobbio et al, 2012;Bonias et al, 2010;Leggat et al, 2010Leggat et al, , 2011McAlearney et al, 2011) emphasized the importance of investigating psychological empowerment as an effect of organizational initiatives to support empowerment; in other words, micro-level studies of employees are important for understanding the effects of organizational initiatives such as highperformance work systems (HPWS).…”
Section: Previous Research On Empowerment Of Clinical Staff In Health...mentioning
confidence: 80%
“…Research confirms that empowering leadership practices, for example, transformational leadership, can influence nurse retention and work engagement. [6,41,42] Some researchers, for example Schuck [43] and de Zulueta, [44] have strongly advocated compassionate leadership, which emphasizes presence and empathy and goes beyond traditional leader-follower roles by seeing leadership as a dynamic shared or distributed process. Last, according to some participants in this study, nurses should consider the impact their negative attitudes have on the image and appreciation of the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
“…According to Faulks et al (2021), empowering leaders aim to assist their team members to develop to their full potential, proactively engage with their best interests, and encourage them to express themselves openly. Additionally, empowering leaders positively affect employees' work engagement (Al Otaibi et al, 2022;Arshad et al, 2022) and their selfleadership, thus contributing to project success (Ahmad et al, 2022). As per Murray et al (2022), when employees feel empowered and safe, they are not reluctant to raise concerns, ask questions, report mistakes, and make suggestions for improvement.…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
“…(2021), empowering leaders aim to assist their team members to develop to their full potential, proactively engage with their best interests, and encourage them to express themselves openly. Additionally, empowering leaders positively affect employees’ work engagement (Al Otaibi et al. , 2022; Arshad et al.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%